A smart experimental technique for the optimization of dielectric elastomer actuator (DEA) systems. (21st August 2015) - Hodgins, M; Rizzello, G; York, A; Naso, D; Seelecke, S
Abstract: In order to aid in moving dielectric elastomer actuator (DEA) technology from the laboratory into a commercial product DEA prototypes should be tested against a variety of loading conditions and eventually in the end user conditions. An experimental test setup to seamlessly perform mechanical characterization and loading of the DEA would be a great asset toward this end. Therefore, this work presents the design, control and systematic validation of a benchtop testing station for miniature silicon based circular DEAs. A versatile benchtop tester is able to characterize and apply programmable loading forces to the DEA while measuring actuator performance. The tester successfully applied mechanical loads to the DEA (including positive, constant and negative stiffness loads) simulating biasing systems via an electromagnetic linear motor operating in closed loop with a force/mechanical impedance control scheme. The tester expedites mechanical testing of the DEA by eliminating the need to build intricate pre-load mechanisms or use multiple testing jigs for characterizing the DEA response. The results show that proper mechanical loading of the DEA increases the overall electromechanical sensitivity of the system and thereby the actuator output. This approach to characterize and apply variable loading forces to DEAs in a single test system will enable faster realization of higher performance actuators.